Preliminary assessment of group composition and activity pattern of the critically endangered Bornean Banded Langur Presbytis chrysomelas chrysomelas in Tanjung Datu National Park - Tukiman, Nur-Aizatul; Abd Rahman, Mohd-Ridwan; Mohammad, Noor-Faezah; Tawie Tingga, Tawie Tingga; Bukhori, Bukhori; Mohd-Azlan, Jayasilan; Denel, Azroie; Muhammad Abu Bakar, Abdul-Latiff; Badrul Munir, Md-Zain (2024)
The Bornean banded langur (Presbytis chrysomelas chrysomelas) is critically endangered species primarily found in Sarawak, Malaysia. Albeit this species is in peril, the ecology knowledge of this endemic species of Borneo is still scarce. Thus, a rapid survey employing total count and scan sampling method was conducted between July to August 2023 at Tanjung Datu National Park (TDNP), Sarawak to observe the social interaction of species with the environment. The behaviour of langur was recorded by employing scanning sampling method at 10 minutes intervals. This study sought to provide preliminary data on behavioural ecology of the Bornean banded langur within the national park. During the survey, three groups (consisting two to seven individuals) and a solitary male Bornean banded langur were recorded. The langurs were observed in both dipterocarp forests and coastal forests within the park. The daily activities of the Bornean banded langurs in TDNP were predominantly resting (31%), moving (29%), feeding (26%), vocalizing (14%), but not engaging in other social activities such as grooming, playing and mating. Knowing the behavioural ecological status as well as understanding ecology by identifying the activity pattern of langur is essential to government authorities and pertinent stakeholders to implement conservation strategies for the Bornean banded langur and their habitats.